NATURAL DISASTERS AND THEIR IMPACT ON CRITICAL INFRASTRUCTURE IN THE UNITED ARAB EMIRATES - Hassan, Faisal Essa Ali Abdallah; Šaljić, Eldar; Kraktus, Ema (The Policy of National Security, 2025)
Climate change is one of the main challenges facing the population around the world. The consequences of these changes have been manifested for decades in various ways, creating disasters that threaten the lives of an increasing number of people. This paper analyses the consequences of the floods that hit the United Arab Emirates on April 16, 2024. After any natural disaster, this flood also calls into question the approach, preparedness and response to this challenge, questioning the success of managing critical infrastructure. This is an important question given that in the last two decades the United Arab Emirates has encountered several floods of a more serious scale. In line with the further development of the consequences of climate change and in response to the challenges they bring with them when it comes to the United Arab Emirates, the authors also propose specific guidelines for the relevant institutions as a way of improving critical infrastructure. A significant area would be to focus on the latest technology in creating superior public-private partnerships that would become modern, national-integrated emergency management systems. The authors used the Risk Management Theory, suggesting ways in which preventive responses can be made. The authors also used content analysis, as well as the observation method.